2022
DOI: 10.1002/ceas.12232
|View full text |Cite
|
Sign up to set email alerts
|

Demands, resources, meaningful work, and burnout of counselors‐in‐training

Abstract: This study examined the relationship between demands, resources, meaningful work, and burnout of counselorsin-training. The results of structural equation modeling indicated that demands and resources significantly predicted burnout of counselors-in-training, whereas meaningful work did not mediate the relationship between resources and burnout. Implications for counselor education are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…This scale uses a 5‐point Likert‐type response, ranging from 1 = Totally disagree to 5 = Totally agree . Considering the aim and participants of this research, we changed the term “work” to “program.” One example item reads, “I have sufficient possibilities to develop myself at my program.” Um & Bardhosh (2022) reported adequate internal reliability ( α = 0.75) with a sample of 243 CITs. Cronbach's α for this sample was .82.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This scale uses a 5‐point Likert‐type response, ranging from 1 = Totally disagree to 5 = Totally agree . Considering the aim and participants of this research, we changed the term “work” to “program.” One example item reads, “I have sufficient possibilities to develop myself at my program.” Um & Bardhosh (2022) reported adequate internal reliability ( α = 0.75) with a sample of 243 CITs. Cronbach's α for this sample was .82.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its enduring impact on their work with clients, researchers have focused on CITs’ challenging duties which can lead them to burnout, across personal, academic, and practical domains (Richardson et al., 2020; Thompson et al., 2011). For instance, Um & Bardhoshi (2022) identified that CITs with more work‐family conflict, workload, and financial strain experienced more severe CIT burnout than those with fewer challenges. In addition to CIT burnout, engagement has been discussed in the counseling literature to understand counselor wellness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations